2017
DOI: 10.1093/annonc/mdx229
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life predicts overall survival in women with platinum-resistant ovarian cancer: an AURELIA substudy

Abstract: NCT00976911.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…OC relapse has a negative psychological and physical impact, highlighting the importance of time without recurrence and the need for effective treatment in the long term [14]. Quality of life predicts overall survival in women with platinum-resistant ovarian cancer as it was demonstrated in AURELIA substudy [15].…”
Section: Discussionmentioning
confidence: 98%
“…OC relapse has a negative psychological and physical impact, highlighting the importance of time without recurrence and the need for effective treatment in the long term [14]. Quality of life predicts overall survival in women with platinum-resistant ovarian cancer as it was demonstrated in AURELIA substudy [15].…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, there have been no analyses published investigating prognostic factors to identify patients with PPSROC!3 who are likely to stop chemotherapy early due to rapid progression. We have addressed this question for women with platinum-resistant ovarian cancer and found that PF and RF remained significant predictors of stopping chemotherapy early; poorer PF, RF, GHS and worse AGIS were independent predictors of shorter OS; PF, RF and GHS were independent predictors of death within 30 days of chemotherapy [5,6]. The importance of this area of research is supported by the recognition that many patients are treated with chemotherapy in their last month or two of life, which is not considered good practice.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal being to identify the subset of patients with a particularly poor prognosis and a short survival in whom supportive care would be a better option than chemotherapy. We have previously reported that low baseline global health status (GHS), role function (RF), physical function (PF), and high abdominal/gastrointestinal symptom score (AGIS) were associated with worse outcomes in patients with platinum-resistant ovarian cancer [5,6]. We considered a range of clinicopathologic characteristics previously shown to have prognostic significance at baseline in patients with PPSROC!3, including performance status (PS), neutrophil lymphocyte ratio, thrombocytosis [7e10], aspects of HRQL, and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In an era when the vast majority of research is still being conducted without input from its intended beneficiaries, the patients, a few salient points have emerged that force us to question this practice. First, a cancer patient's self‐reported quality of life (QOL) can predict their own survival, independent of other factors . This has been demonstrated in several studies evaluating patients with cancer in general and has long been studied specifically in lung cancer .…”
Section: Introductionmentioning
confidence: 99%
“…First, a cancer patient's self-reported quality of life (QOL) can predict their own survival, independent of other factors. [1][2][3][4][5][6][7][8][9][10][11][12][13] This has been demonstrated in several studies evaluating patients with cancer in general 4,10-13 and has long been studied specifically in lung cancer. [1][2][3][5][6][7][8][9] In one study, QOL was identified as a more powerful predictor of outcome compared to standard measures such as Karnofsky performance score or staging.…”
Section: Introductionmentioning
confidence: 99%